Quality assessment of eggs packed under modified atmosphere - Giampietro-Ganeco, Aline [UNESP]; Borba, Hirasilva [UNESP]; Scatolini-Silva, Aline Mary [UNESP]; Boiago, Marcel Manente; Souza, Pedro Alves de [UNESP]; Malagoli de Mello, Juliana Lolli [UNESP] (Univ Federal Lavras-ufla, 2015)
Eggs are perishable foods and lose quality quickly if not stored properly. From the moment of posture to the marketing of egg, quality loss occurs through gas exchange and water through the pores of the shell with the external environment and thus, studies involving modified atmosphere packaging are extremely important. The aim of the present study is to assess the internal quality of eggs packed under modified atmosphere and stored at room temperature. Six hundred and twelve fresh commercial eggs from 38-week old Hisex White laying hens were used. The present study was conducted in a completely randomized experimental design in a 4 x 4 + 1 factorial arrangement [vacuum, vacuum with oxygen gas (O-2) absorbent, vacuum with oxygen gas (O-2) and carbon dioxide (CO2) absorbents, vacuum with oxygen gas (O-2) absorbent and carbon dioxide (CO2) gas generator; storage times (7, 14, 21 and 28 days), control group (fresh eggs)], with three repetitions (12 eggs each). The following factors were assessed: weight maintenance during storage; Haugh unit; color and yolk index. The modified atmosphere packaging maintained the weight of the eggs during a period of 28 days. Vacuum packaging with O-2 absorbent and CO2 gas generator was more efficient in maintenance of egg quality, based on the values of Haugh unit and yolk index. The luminosity of the yolk was preserved during the 28 storage days in all of the packaging types used. The vacuum packaging with O-2 gas absorbent and CO2 gas generator provide an increase in internal egg quality.

Os ovos são alimentos perecíveis e perdem sua qualidade rapidamente se não forem armazenados corretamente. Do momento da postura até a comercialização do ovo, ocorre perda de qualidade por meio de trocas gasosas e de água, através dos poros da casca com o ambiente externo, sendo de extrema importância os estudos que envolvam embalagens com atmosfera modificada. O estudo foi realizado com o objetivo de avaliar a qualidade interna de ovos embalados com atmosfera modificada e armazenados em temperatura ambiente. Foram armazenados 612 ovos frescos comerciais de galinhas da linhagem Hisex Branca (HSB) com 38 semanas de idade. Utilizou-se um DIC em esquema fatorial 4x4+1 [vácuo, vácuo com sequestrador de gás oxigênio (O2), vácuo com sequestrador de gás oxigênio (O2) e de gás carbônico (CO2), vácuo com sequestrador de gás oxigênio (O2) e gerador de gás carbônico (CO2) e períodos de armazenamento 7, 14, 21 e 28 dias + testemunha - ovos frescos], com 3 repetições de 12 ovos cada. As características avaliadas foram: manutenção de peso durante armazenamento, unidade Haugh, índice gema e coloração da gema. As embalagens com atmosfera modificada mantiveram os pesos dos ovos por um período de 28 dias e a embalagem 4 (vácuo com sequestrante de O2 e geradores de CO2) foi a que apresentou melhores valores para a unidade Haugh e para o índice gema. A gema preservou sua luminosidade durante os 28 dias de armazenamento, independente da embalagem utilizada. O vácuo das embalagens avaliadas proporcionou efeito positivo na qualidade interna dos ovos e estes, quando armazenados em estojos que continham sequestrador de gás oxigênio (O2) e gerador de gás carbônico (CO2), preservaram ainda mais a qualidade de suas características internas.
Avaliação da qualidade de ovos embalados sob atmosfera modificada
Keywords: Storage; Sachet; Vacuum; Armazenamento; Sachês; Vácuo